Spatial Lag Model for Apartment Prices in Pardubice Region - Pozdílková, Alena; Marek, Jaroslav (Slovenská technická univezita v Bratislave, 2018)
The article is devoted to modelling the relationship of apartment prices between neighbouring small municipalities within Pardubice region. A spatial lag model will be used for the calculation, and the unknown parameters will be estimated using the least squares method. This model is often used to describe geo-informational phenomena.
Spatial Lag model pro ceny bytů v Pardubickém kraji
Keywords: spatial modelling; Spatial Lag Model; factor model; weights matrix; estimation of unknown parameters; exploratory visualization; spatail lag versus spatial error models; prostorové modelování; prostorový lag model; faktorový model; matice vah; odhad neznámých parametrů; vizualizace